ANALISIS FAULT FRACTURE DENSITY (FFD) PADA ZONA RAWAN BENCANA TANAH LONGSOR KABUPATEN NGAWI - Mutiara Jannah, Dea; Nugroho Budi Wibowo; Hana Rosyida; Fathunajah Elsha C.; Salma Khoirunnisa; Indar Mery Sulya A.; Icha Khaerunnisa (KURVATEK, 2025)
Ngawi is one of the areas in East Java province with an area that has topographic variations in the form of lowlands and highlands, because of its location on the slopes of Mount Lawu. There are several areas in Ngawi Regency that have the potential to be prone to landslides, which were then identified as suitable between the landslide hazard map which was derived from combining rainfall parameters, slope slope and geological conditions. Next, the landslide hazard map was compared with the FFD map produced from DEM (Digital Elevation Model) alignment analysis. The resulting landslide map is in accordance with the FFD map produced, namely in Sine sub-district, Ngrambe sub-district, Jogorogo sub-district and Kendal sub-district.